Dopamine in high-risk populations: A comparison of subjects with 22q11.2 deletion syndrome and subjects at ultra high-risk for psychosis. (28th February 2018) - Vingerhoets, Claudia; Bloemen, Oswald J.N.; Boot, Erik; Bakker, Geor; de Koning, Mariken B.; da Silva Alves, Fabiana; Booij, Jan; van Amelsvoort, Thérèse A.M.J.
Abstract: Striatal dopamine (DA) dysfunction has been consistently reported in psychotic disorders. Differences and similarities in the pathogenesis between populations at clinical and genetic risk for developing psychosis are yet to be established. Here we explored markers of dopamine (DA) function in subjects meeting clinically ultra-high risk criteria for psychosis (UHR) and in subjects with 22q11.2 deletion syndrome (22q11DS), a genetic condition associated with significant risk for developing psychotic disorders. Single Photon Emission Computed Tomography (SPECT) with 123 I-labelled iodobenzamide ([ 123 I]IBZM) was used to measure striatal DA D2/3 receptor binding potential (D2 R BPND ). Also, peripheral DAergic markers were assessed in serum and urine (plasma prolactin (pPRL), plasma homovanillic acid (pHVA) and urine DA(uDA)). No significant difference in striatal D2 R BPND was found between UHR and 22q11DS subjects. Compared to UHR subjects, pPRL and pHVA were lower and uDA levels were higher in the 22q11DS subjects. However, after correcting for age and gender, only pPRL as significantly lower in the 22q11DS patients. These results may suggest that there are differences in DAergic markers between subjects with UHR and with 22q11DS that may reflect differences in the pathways to psychosis. However, bigger samples are needed to replicate these findings. Highlights: This study compared dopaminergic markers between two groups at risk for psychosis. 22q11DS and UHR subjects differ in peripheral dopaminergic markers. This suggests that different dopaminergic changes are related to risk of psychosis. These findings increase our understanding of pathways leading to psychotic disorders.